Kebijakan Publik dalam Perspektif Hukum: Studi Kasus Implementasi Undang-Undang Cipta Kerja dengan Metode Studi Dokumen - Mulfirana; Taufik, Moh; Wiratman, Ajus (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The enactment of Law No. 11 of 2020 on Job Creation (UU Cipta Kerja) aims to simplify bureaucracy, attract investment, and create job opportunities in Indonesia. However, its implementation has raised legal uncertainties, particularly following the Constitutional Court’s ruling that deemed the law conditionally unconstitutional. Concerns have also emerged from labor unions and environmental organizations regarding its potential impact on workers’ rights and environmental sustainability. This study analyzes the legal and public policy perspectives of UU Cipta Kerja by evaluating its impact on investment, employment, and legal certainty. Using a qualitative approach with a document study method, this research examines legal documents, policy regulations, and court rulings, supplemented by expert interviews. The findings reveal that the law contributed to an 8.3% increase in Foreign Direct Investment (FDI) in its first year, reaching IDR 454 trillion in 2021. However, contract workers increased by 25%, raising concerns about job security. Additionally, five constitutional challenges were filed against the law in 2023, reflecting legal uncertainty. Weaknesses in environmental oversight were also identified due to relaxed business licensing requirements. These findings suggest that while UU Cipta Kerja supports investment growth, stronger legal safeguards and monitoring mechanisms are needed to ensure balanced benefits for all stakeholders. This study contributes to discussions on labor and investment policies by emphasizing the need for inclusive regulatory reforms that align economic growth with legal stability and worker protection.